FNKSDA SEBAGAI WUJUD GERAKAN ISLAM NUSANTARA “HIJAU’ - Listiana Asworo; Nuruddin Al Akbar (Aqlam: Journal of Islam and Plurality, 2019)
Abstract. This study seeks to get out of mainstream thinking in environmental studies that are based on Eurocentric logic. Mainstream studies emphasize the "secular" pattern of "universal" environmental ideologies. There are few works that try to explore the idea of saving the environment based on local wisdom and local religious traditions. This study would like to provide another perspective that the environmental struggle can be upheld by based on religious ideas that grow in Indonesia which are sharpened by the tradition of environmental movements that arise in the Western context (specifically the green Marxism movement). The process of dialogue between the East and West cultures was evident from the presence of the FNKSDA (Nahdliyin Front for the Sovereignty of Natural Resources) which was initiated by the Nahdliyin youth. FNKSDA can be interpreted as a concrete form of "dialogue" in the traditions of Nahdliyin and Marxism, especially regarding the commitment to preserve the environment from the threat of capitalism. This movement itself has a praxis tendency, meaning that it not only cares about the design of environmental ideologies but also seeks to carry out environmental advocacy processes in various vulnerable areas. The model of this dialogue, for example, can be found in a variety of FNKSDA activities that do not use old typical of Nahdliyin such as "Ngaji", "Fikih" but also dialogue with Western terms such as capitalism, internal contradictions of Capitalism and Marxism. Key Words: FNKSDA, Environmental Theology, Green Marxism, Religious Environmental movement. Abstrak: Studi ini berupaya keluar dari corak berfikir mainstream dalam studi lingkungan yang berpijak pada logika Eurosentris. Studi mainstream  dimana lebih menekankan pada ideologi lingkungan "universial" yang bercorak "sekuler". Sedikit karya yang mencoba lebih menggali ide penyelamatan lingkungan yang lebih berbasis pada kearifan lokal dan tradisi keagamaan lokal. Studi ini ingin memberikan prespektif lain bahwa perjuangan lingkungan bisa ditegakkan dengan berfondasi pada ide keagamaan yang tumbuh di indonesia yang dipertajam dengan tradisi gerakan lingkungan yang muncul dalam konteks Barat (secara spesifik gerakan Marxisme hijau). Proses dialog kultur Barat-Timur tersebut itulah yang nampak dengan hadirnya gerakan FNKSDA (Front Nahdliyin untuk Kedaulatan Sumber Daya Alam) yang diinisasi oleh kalangan muda Nahdliyin. FNKSDA dapat dimaknai sebagai wujud konkrit “dialog” tradisi Nahdliyin dan Marxisme, terkhusus mengenai komitmen menjaga kelestarian lingkungan dari ancaman kapitalisme. Gerakan ini sendiri punya tendensi praxis, artinya tidak hanya hirau terhadap rancang bangun ideologi lingkungan tetapi juga berupaya melakukan proses advokasi lingkungan di berbagai wilayah rentan. Corak dialog ini misalnya dapat ditemukan dalam berbagai kegiatan FNKSDA yang tidak lupus menggunakan term khas kaum Nahdliyin seperti “Ngaji”, “Fikih” tetapi juga mendialogkannya dengan istilah Barat seperti term Kapitalisme, kontradiksi internal Kapitalisme, dan Marxisme. Kata Kunci: FNKSDA; Teologi Lingkungan; Marxism Hijau; Gerakan Lingkungan Beragama.